Internet-based cognitive-behavioural writing therapy for reducing post-traumatic stress after severe sepsis in patients and their spouses (REPAIR): results of a randomised-controlled trial. Issue 3 (9th March 2022) - Gawlytta, Romina; Kesselmeier, Miriam; Scherag, Andre; Niemeyer, Helen; Böttche, Maria; Knaevelsrud, Christine; Rosendahl, Jenny
Abstract : Objectives: To investigate the efficacy, safety and applicability of internet-based, therapist-led partner-assisted cognitive-behavioural writing therapy (iCBT) for post-traumatic stress disorder (PTSD) symptoms after intensive care for sepsis in patients and their spouses compared with a waitlist (WL) control group. Design: Randomised-controlled, parallel group, open-label, superiority trial with concealed allocation. Setting: Internet-based intervention in Germany; location-independent via web-portal. Participants: Patients after intensive care for sepsis and their spouses of whom at least one had a presumptive PTSD diagnosis (PTSD-Checklist (PCL-5)≥33). Initially planned sample size: 98 dyads. Interventions: ICBT group: 10 writing assignments over a 5-week period; WL control group: 5-week waiting period. Primary and secondary outcome measures: Primary outcome: pre–post change in PTSD symptom severity (PCL-5). Secondary outcomes: remission of PTSD, depression, anxiety and somatisation, relationship satisfaction, health-related quality of life, premature termination of treatment. Outcomes measures were applied pre and post treatment and at 3, 6 and 12 months follow-up. Results: Twenty-five dyads representing 34 participants with a presumptive PTSD diagnosis were randomised and analysed (ITT principle). There was no evidence for a difference in PCL-5 pre–post change for iCBT compared with WL (mean difference −0.96, 95% CI (−5.88 to 3.97), p=0.703). No adverse events were reported. Participants confirmed the applicability of iCBT. Conclusions: ICBT was applied to reduce PTSD symptoms after intensive care for sepsis, for the first time addressing both patients and their spouses. It was applicable and safe in the given population. There was no evidence for the efficacy of iCBT on PTSD symptom severity. Due to the small sample size our findings remain preliminary but can guide further research, which is needed to determine if modified approaches to post-intensive care PTSD may be more effective. Trial registration number: DRKS00010676.